Atomic force microscopy-based antibody recognition imaging of proteins in the pathological deposits in Pseudoexfoliation Syndrome - Creasey, R.; Sharma, S.; Gibson, C.; Craig, J.; Ebner, A.; Becker, Thomas; Hinterdorfer, P.; Voelcker, N. (ELSEVIER, 2011)
The phenomenon of protein aggregation is of considerable interest to various disciplines, including the field of medicine. A range of disease pathologies are associated with this phenomenon. One of the ocular diseases hallmarked by protein aggregation is the Pseudoexfoliation (PEX) Syndrome. This condition is characterized by the deposition of insoluble proteinaceous material on the anterior human lens capsule. Genomic and proteomic analyses have revealed an association of specific genetic markers and various proteins, respectively, with PEX syndrome. However, the ultrastructure of the protein aggregates is poorly characterized. This study seeks to build capacity to determine the molecular nature of PEX aggregates on human lens capsules in their native state by AFM-based antibody recognition imaging. Lysyl oxidase-Like 1 (LOXL1), a protein identified as a component of PEX aggregates, is detected by an antibody-modified AFM probe. Topographical AFM images and antibody recognition images are obtained using three AFM-based techniques: TREC, phase and force–volume imaging. LOXL1 is found to be present on the lens capsule surface, and is localized around fibrous protein aggregates. Our evaluation shows that TREC imaging is best suited for human tissue imaging and holds significant potential for imaging of human disease tissues in their native state.